Agricultural development for peace - Tony Addison (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
Agricultural development can contribute significantly to peace by raising incomes and employment, thereby reducing the social frustrations that give rise to violence. Agricultural growth also generates revenues for governments, allowing them to redress the grievances of disadvantaged populations. In this way, growth can be made more equitable, an effect that is enhanced if inequalities in access to natural capital, especially to land, are addressed as well. Agriculture is critical for countries rebuilding from war, especially in making recovery work for the poor. And by raising per capita incomes, agricultural development underpins new democracies. Agricultural development thereby supports political strategies for peace-building and democratization. – agriculture ; conflict ; peace ; international trade
Keywords: N40; O13; Q18; 330; Landwirtschaft; Sozialer Konflikt; Frieden